Global Imbalances and the Asian Economies: Implications for Regional Cooperation - Barry Eichengreen (Asian Development Bank (ADB), 2006)
This paper asks how Asia should prepare for the disorderly correction of global imbalances. It recommends tightening monetary policy and allowing Asian currencies to appreciate as a way of achieving a better balance between internal and external demand. Leaving the overall level of demand unchanged requires that this monetary tightening be complemented by some relaxation of fiscal policy. But because the scope for fiscal support of domestic demand differs across countries, so too does the optimal degree of monetary tightening and exchange rate adjustment. This observation makes clear that an attempt to suppress intra-Asian exchange rate movements would be counterproductive in this context. Other policy measures that produce effects over longer horizons that can further contribute to the rotation of demand away from exports to the US include the development of Asian financial markets and the completion of an Asian free trade area. These policy adjustments will occur most easily if they are coordinated within Asia.
hdl:11540/2563
Keywords: F41; F42; 330; Asia economies; global imbalances; international economics; economic integration; regional cooperation